Syntactical Errors in Students’ Abstract - Frisyi Fitriyani Fauziyah (Journal on Education, 2023)
This research focuses on investigating syntactical errors found in the students’ abstract. It is expected that the result of research can provide useful information about students’ problem in writing abstract, particularly problem in syntax. This research aims to find out types of syntactical errors made by the students in writing abstracts and to discover the reason why the students make syntactical errors in writing abstracts. Therefore, the research tries to find out the way to overcome syntactical errors in students’ abstracts. The method of this research is a descriptive qualitative study that constitutes a study with a grounded theory as data analysis. This research is conducted to find out types of syntactical errors made by the students in writing abstract, to discover the reason why the students make syntactical errors in writing abstract and to find out the way to overcome syntactical errors in students’ abstract. There are some conclusions as the results of the research. Firstly, the syntactical errors which often appear are minor syntactical units (article, preposition, genitive and plural of noun). Secondly, lack of attention given by the lectures or students to the minor syntactical units when they taught or learned can be the influence of the students’ mother language (Bahasa Indonesia) that influences their foreign language (English).